Mengupas Motif & Kepuasan Pengguna Blackberry di Indonesia - Martinus, Handy (Humaniora, 2011)
Lately, BlackBerry is familiar in many people, especially due to the publicity of problems between Indonesia?s communication and information ministry and Canada-based BlackBerry developer, Research in Motion (RIM). In doing the research, the writer spread pre-questionnaire to 30 respondents to validity and reliability test. Afterwards, the writer gave the questionnaires to 100 respondents as BlackBerry users in employees? limitation. The result is that there is satisfaction towards information, private identity, integration, and social interaction, and also towards entertainment after using BlackBerry.